Regulated expression of the tyrosine hydroxylase gene by epidermal growth factor. - Lewis, E J (1987)
The addition of epidermal growth factor (EGF) to cultures of the rat PCG2 pheochromocytoma cell line increased the level of RNA coding for tyrosine hydroxylase (TH). A region of DNA containing 5'-flanking sequences of the TH gene was fused to a heterologous gene and transfected into a rat anterior pituitary cell line, GH4. The TH gene sequences from +27 to -272 contained information sufficient for the induction of TH by EGF. Two regions within this TH DNA were extensively homologous to the EGF regulatory element of the rat prolactin gene.